PENGARUH KOMITMEN ORGANISASI TERHADAP KINERJA KAYAWAN PADA PT.SENTRA SURYA ABADI RANGKASBITUNG - Muhi Mukti; Cucu Putri Dewi (Universitas La Tansa Mashiro, 2020)
This study aims to determine the effect of organizational commitment on employee performance at PT. Sentra Surya Abadi Rangkasbitung. The research method used is a quantitative method with a population of all employees at PT.Sentra Surya Abadi Rangkasbitung, with a sample of 50 employees. The data analysis techniques in this study include test requirements for data analysis (normality test, autocorrelation test and heterodasticity test), simple linear regression analysis, correlation analysis, analysis of determination coefficient and t test, in SPSS 20 For Windows. From the results of the study showed that organizational commitment has a positive effect on employee performance as evidenced by the simple linear regression equation Y = 1.912 + 0.950X and R square of 0.912 or 91.2% and based on the t test organizational commitment has a significant effect on employee performance because of the significant value small of 0.05 (α ) which is equal to 0,000. Thus it can be concluded that there significant is an influence between organizational commitment to employee performance at PT.Sentra Surya Abadi Rangkasbitung.